Management and Followup of Complicated Crown Fractures in Young Patients Treated with Partial Pulpotomy - Francisco Ojeda-Gutierrez; Brenda Martinez-Marquez; Soraya Arteaga-Larios; M. Socorro Ruiz-Rodriguez; Amaury Pozos-Guillen (Hindawi Limited, 2013)
Two cases of young patients with traumatized permanent teeth having complicated crown fractures are reported. Endodontic management included partial pulpotomy by the Cvek technique; restorative management included resin restoration and reattachment of the teeth fragments. Treatments were considered successful in all cases according to the following criteria: absence of clinical symptoms, absence of X-ray signs of pathology, and presence of pulpal vitality 6 to 25 months after treatment.